Extração e purificação de ficobiliproteínas de Spirulina (Arthrospira) platensis com líquidos iônicos próticos - Rodrigues, Renata Débora Pinto (2017)
Bioactive compounds extracted from natural renewable sources have attracted increased interest from both industry and academia. Cyanobacteria possess a broad range of colored components including carotenoids, chlorophyll, and phycobiliproteins. Phycobiliproteins are pigments accessories photosynthetic potential for use in various applications - dyes in food and cosmetics, fluorescent tags in biomedical research, nutraceutical and pharmaceutical applications. Considerations to obtain of microalgae phycobiliproteins may include: choosing the most suitable method of extraction, solvent and extraction of the main setting parameters. While phycobiliproteins extraction classical methods are reproducible and show good yields are generally time consuming and require the use of elevated temperatures and / or large volumes of solvent, which can cause thermal denaturation or chemical transformation of the products of interest. Therefore, the development of new extraction green techniques permitting the transfer of the results obtained in laboratory scale for industrial need for greater biotechnological exploitation of these and other products from microalgae. In this work, the performance of ionic liquids as solvents in phycobiliproteins extraction from Spirulina (Arthrospira) platensis was evaluated using three different methods: conventional (heating + agitation), microwave and ultrasound. The extraction was optimized using a central composite design and response surface methodology. The effects of temperature, pH, biomass:solvent ratio and power were studied to determine the best extraction conditions of extraction. The results showed that the protic ionic liquids were capable of extracting phycobiliproteins from microalgae, being more efficient than buffer and aprotic ionic liquid [Bmim][Cl]. The effect of pH was more significant in conventional and ultrasound methods. In microwave-assisted extraction, the irradiation power was the most important variable. The allophycocyanin was extracted in larger quantities (13.30 mg.g-1), followed by phycocyanin (10.87 mg.g-1) and phycoerythrin (4.22 mg.g-1). This method of extraction showed advantages over the extraction time, productivity, purity and energy consumption across the conventional method and ultrasound-assisted extraction. The SEM revealed that the microwave caused more impacts on the cellular structure of the microalgae compared to other methods. In the study of operating conditions, microwave-assisted extraction was considered the best technique, using 2-HEAA + 2-HEAF as solvent at power of 62 W, pH 7.0, biomass:solvent ratio 10 mL.g-1 and 2 min of extraction. A savings of 99.94% in electricity consumption was obtained with the use of microwaves compared to conventional method. The extraction method proposed in this work proved to be efficient for obtaining S. platensis phycobiliproteins. By the applied purification methodology the following yield and purity were obtained for phycocyanin, allophycocyanin and phycoerythrin: 15% and 1.22; 11.33% and 1.03; 11.92% and 0.71, respectively. The degree of purity achieved allows the application of these pigments in food and cosmetics. Polyacrylamide gel electrophoresis (SDS-PAGE) showed that the phycobiliproteins have molecular weight around 20 KDa. Preliminary studies on the recovery and reuse of the ionic liquid were conducted, proving the possibility of reuse of these solvents.